The illusion of aircrews' fatigue risk control. (March 2020) - Bourgeois-Bougrine, Samira
Abstract: In the fragmented European airline sector, companies are operating in a highly competitive environment amid rising cost of labour, fuel and airport fees. Fatigue risk management systems (FRMS) contribute to flexibly optimizing crew "utilization" through deviations and derogations from prescriptive European limits on duty times and rest durations. However, the flexibility gained comes at a price: it introduces an internal bureaucracy to mitigate the risks associated with crewmembers' fatigue and to develop, maintain and document fatigue related safety performance indicators. This paper questions the effectiveness of the FRMS framework and suggests that the bureaucratic process of the FRMS provides an illusion of fatigue risk control. More specifically four questions will be addressed: Why an operator needs an FRMS? Why the FRMS involves a bureaucratic process? What are the limits of the bureaucratic accountability of the FRMS and, finally, how might we manage fatigue risk effectively while keeping everyone happy, the shareholders as well as stakeholders? Highlights: An operator needs an FRMS when the nature of the deviations and derogations from FTL regulations is critical The FRMS bureaucratisation is associated to SMS principles and ISO31000 guidelines The limits to the FRMS bureaucratic accountability relates to probabilistic approach of fatigue risk management, conflicts of interest and safety climate The implications for effective fatigue management are : policy changes, labour management and sociotechnical solutions